Smart Rotor Modeling Aero-Servo-Elastic Modeling of a Smart Rotor with Adaptive Trailing Edge Flaps - Bergami, Leonardo (Research Topics in Wind Energy,, 2014)
A smart rotor is a wind turbine rotor that, through a combination of sensors, control units and actuators actively reduces the variation of the aerodynamic loads it has to withstand. Smart rotors feature a promising load alleviation potential, and might provide the technological breakthrough required by the next generation of large wind turbine rotors. The book presents the aero-servo-elastic model of a smart rotor with Adaptive Trailing Edge Flaps for active load alleviation, and provides an insight on the rotor aerodynamic, structural, and control modeling. A novel model for the unsteady aerodynamics of an airfoil section with flap is presented, and coupled with a multi-body structural representation. A smart rotor configuration is proposed, where the Adaptive Trailing Edge Flaps extend along the outer 20 % of the blade span. Linear Quadratic and Model Predictive algorithms are formulated to control the flap deflection.  The potential of the smart rotor is finally confirmed by simulations in a turbulent wind field. A significant reduction of the fatigue loads on the blades is reported:  the flaps, which cover no more than 1.5 % of the blade surface, reduce the fatigue load by 15 %; a combination of flap and individual pitch control allows for fatigue reductions up to 30 %.